Use of Telone II and Temik 15G to Improve Yields and Returns of Cotton Grown in Northwest Florida Fields Infested with Reniform Nematodes - D. J. Zimet; J. L. Smith; Jimmy R. Rich; R. A. Kinloch; Timothy D. Hewitt (EDIS)
This study was conducted to determine the economic return on investment for growers using different application rates of Telone II and Temik 15G. Incremental costs per pound of increased lint yield due to nematicide addition, net return per pound of increased lint yield, and partial net return per acre were calculated for treatments (Boehlje and Eidman, 1984). This is EDIS document FE 319, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published November 2004.